FROM QUOTAS TO SUBSTANCE: IMPLEMENTING REGIONAL REGULATION NO. 9 ON GENDER MAINSTREAMING IN DPRD BOJONEGORO - Elsa Muizzatul Abadiyah; Septi Wulandari; Rupiarsieh Rupiarsieh (Journal of Social Politics and Governance (JSPG), 2026)
This study is motivated by persistent gender disparities showing that increased women’s numerical representation in local legislatures has not ensured the substantive integration of gender perspectives. It examines the implementation of Regional Regulation No. 9 of 2025 on Gender Mainstreaming in the Bojonegoro District Parliament. The research addresses the gap between the formal adoption of gender mainstreaming policy and its limited operationalization within the legislative, budgeting, and oversight functions of the DPRD. This study is grounded in substantive representation theory and the gender mainstreaming framework to analyze institutional dynamics of gender-responsive policy implementation. The research employs a qualitative case study approach using in-depth interviews, observation, and document analysis, with data analyzed through the Miles-Huberman interactive model supported by NVivo coding to identify patterns of PUG implementation within the DPRD. The findings show that the implementation of Regional Regulation No. 9 of 2025 remains largely normative due to the absence of technocratic instruments translating the PUG mandate into concrete legislative procedures. Moreover, the uneven distribution of women in strategic positions limits the DPRD’s institutional capacity to consistently integrate gender perspectives. Although female legislators demonstrate substantive contributions, these remain individual rather than institutionalized due to weak organizational support and limited inter-institutional coordination.